Information on new drugs at market entry: retrospective analysis of health technology assessment reports versus regulatory reports, journal publications, and registry reports. (26th February 2015) - Köhler, Michael; Haag, Susanne; Biester, Katharina; Brockhaus, Anne Catharina; McGauran, Natalie; Grouven, Ulrich; Kölsch, Heike; Seay, Ulrike; Hörn, Helmut; Moritz, Gregor; Staeck, Kerstin; Wieseler, Beate
Abstract : Background When a new drug becomes available, patients and doctors require information on its benefits and harms. In 2011, Germany introduced the early benefit assessment of new drugs through the act on the reform of the market for medicinal products (AMNOG). At market entry, the pharmaceutical company responsible must submit a standardised dossier containing all available evidence of the drug's added benefit over an appropriate comparator treatment. The added benefit is mainly determined using patient relevant outcomes. The "dossier assessment" is generally performed by the Institute for Quality and Efficiency in Health Care (IQWiG) and then published online. It contains all relevant study information, including data from unpublished clinical study reports contained in the dossiers. The dossier assessment refers to the patient population for which the new drug is approved according to the summary of product characteristics. This patient population may comprise either the total populations investigated in the studies submitted to regulatory authorities in the drug approval process, or the specific subpopulations defined in the summary of product characteristics ("approved subpopulations"). Objective To determine the information gain from AMNOG documents compared with non-AMNOG documents for methods and results of studies available at market entry of new drugs. AMNOG documents comprise dossier assessments done by IQWiG and publicly available modules of company dossiers; non-AMNOG documents comprise conventional, publicly available sources—that is, European public assessment reports, journal publications, and registry reports. The analysis focused on the approved patient populations. Design Retrospective analysis. Data sources All dossier assessments conducted by IQWiG between 1 January 2011 and 28 February 2013 in which the dossiers contained suitable studies allowing for a full early benefit assessment. We also considered all European public assessment reports, journal publications, and registry reports referring to these studies and included in the dossiers. Data analysis We assessed reporting quality for each study and each available document for eight methods and 11 results items (three baseline characteristics and eight patient relevant outcomes), and dichotomised them as "completely reported" or "incompletely reported (including items not reported at all)." For each document type we calculated the proportion of items with complete reporting for methods and results, for each item and overall, and compared the findings. Results 15 out of 27 dossiers were eligible for inclusion and contained 22 studies. The 15 dossier assessments contained 28 individual assessments of 15 total study populations and 13 approved subpopulations. European public assessment reports were available for all drugs. Journal publications were available for 14 out of 15 drugs and 21 out of 22 studies. A registry report in ClinicalTrials.gov was available for all drugs and studies; however, only 11 contained results. In the analysis of total study populations, the AMNOG documents reached the highest grade of completeness, with about 90% of methods and results items completely reported. In non-AMNOG documents, the rate was 75% for methods and 52% for results items; journal publications achieved the best rates, followed by European public assessment reports and registry reports. The analysis of approved subpopulations showed poorer complete reporting of results items, particularly in non-AMNOG documents (non-AMNOG versus AMNOG: 11% v 71% for overall results items and 5% v 70% for patient relevant outcomes). The main limitation of our analysis is the small sample size. Conclusion Conventional, publicly available sources provide insufficient information on new drugs, especially on patient relevant outcomes in approved subpopulations. This type of information is largely available in AMNOG documents, albeit only partly in English. The AMNOG approach could be used internationally to develop a comprehensive publication model for clinical studies and thus represents a key open access measure.